Interpretasi Pragmatik Kontroversi Kakek Penjual Es Gabus dalam Wacana Digital - Ridho Sastro Panjaitan; Grace Evelyn Hutabarat; Tabita Tesalonika Simaremare; Mutiara Aprilia; Mannawa Salwa; Herning Puspitarini; M. Oky F. Gafari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This study analyzes pragmatic phenomena in digital communication, particularly those related to speech acts and their impact on public perception in the controversial case of an ice cube seller accused without clear basis by the authorities. This study applies a qualitative approach with a pragmatic analysis method based on discourse analysis. Data sources were obtained from online media news, social media posts, and official statements circulating in the digital public space. The analysis techniques used include identifying types of speech acts, interpreting implied meanings based on context, and analyzing public responses. The results show that statements from the authorities contain implications that trigger negative views even though they are not supported by strong evidence. This results in perlocutionary effects in the form of social stigma, reputational damage, and psychological stress for the victim. Conversely, the victim's communication strategies, which include being polite, defensive, and informative, can build a positive image and attract public sympathy. Furthermore, social media plays a crucial role in accelerating the spread of meaning and strengthening the construction of opinions through mass support and criticism. This research makes a significant contribution to enriching the study of pragmatics in the context of digital communication and emphasizes the importance of language ethics, media literacy, and pragmatic awareness in creating responsible public communication.